Developmental pathophysiology of the hip - Guglielmone, Oscar (Cirugía del Uruguay, 1973)
Normal hip development follows a pre-established schedule imprinted into its genes. During fetal development the muscles which participate in skeleton remodellation, appear. If muscle structure is altered due to any genetic or acquired factor, its function becomes etiogenic and produces skeleton alterations which affect the joints in particular. Myodysplasia alters its normal development by means of severa! mechanisms: 1 . Increase in pressure between joint components. 2. Morp).ological alterations of collum ( neck). 3. Malfunction of joints which tend to dislocate. Etiogenic activity of dysplasic muscles acts on movable segment of hip, i. e. upper end of femur. Alterations of cotyloid cavity ( acetabulum) are secondary to femoral alterations. ''here is delay in appearence and growth of epiphysis due to excessive compression which affects its circulation. In extreme cases this results in total ischemia with necrosis of epiphysis. Normal evolution of femur collum stops, re&ulting in valgus and anteversion in variable degree, due to disharmonic acttvi,y- of muscles. By reason of same mechanism, normal relationship of cotyloid cavity (acetabulum) with epiphysis is lost. Morphology of cotyloid cavity (acetabulum) is altered due to abnormal position of head. This abnormal position is due to morphological alterations of collum and to dislocating action of dysplasic muscles. Consequently it can be classified as a secondary dysplasia. Sequel!a in mild forms i¡ represented by an apparently normal cotyloid cavity ( acetabulum), which however is lacking in depth; this can be detected by increased thickness of cotyloid cavity (acetabulum). lt is called pre-dislocation. In more serious forms the cotyloid roof ceiling ( acetabulum) is altered so that it is vertically broad with slanting roof ( ceiling. insufficiently deep and very thick. This is termed subdislocation. Finally, in congenital dislocation there is dillocated head and altered epiphysis. Cotyloid cavity ( acetabulum) is small in all its diameters and bottom is thin, thus differing from abovementioned cases.